Avaliação da medida de tenacidade do concreto reforçado com fibras de aço - Arif, Mohammed Adel (2014)
In the concrete might occur cracks, due to the combination of residual stresses, cure or hydration, fluency effects, retraction and temperature effect. The objetive of incorporating steel fibers to concrete is to control the micro-cracking during aplication of loads and also improve the mechanical and residual resistance to fracturing properties . The toughness of steel fiber reinforced concrete is a fundamental property to control cracking and is determinated by flexural bending test of prismatic beams. The advantages to use SFRC in the civil construction are: better cavitation resistance, improves the strength impact plus the shock thermal and increase the ductility by delaying the crack propagation in the concrete structural elements that is subjected to the tension or tension by flexural. This study, examines experimentally the mechanicals behavior of prismatic specimens of SFRC s toughness, according to the international recommendations of ASTM C1609 (2010), EN 14651 (2007) e JSCE-SF4 (1984). On next phase, the research sought to evaluate the influence of compressive strength and the fiber rate s behavior. The experimental program consisted in two matrices of 30 MPa and 40 MPa with two dosages of fibers corresponding to 60 kg/m³ and 30 kg/m³ (0,77 % and 0,38 % in volume) formed four composite of fibers. 64 prismatic specimens were cast to evaluate the tenacity and 132 cylindrical specimens to characterize the SFRC through the compression tests, modulus of elasticity and tensile by diametric compression (Brazilian test). In relation to the method of tests, the result shows that the increasing toughness of SFRC was higher when the fiber content increased the composite compared to the change in compressive strength. The EN 14651 that uses notched specimens, it is interesting method to determine the toughness of steel fiber reinforced concrete, because the method obtained lower coefficient of variation for toughness values and the crack it always propagates in the plane of the notch.